2016
DOI: 10.1117/12.2222966
|View full text |Cite
|
Sign up to set email alerts
|

Software defined multi-spectral imaging for Arctic sensor networks

Abstract: Availability of off-the-shelf infrared sensors combined with high definition visible cameras has made possible the construction of a Software Defined Multi-Spectral Imager (SDMSI) combining long-wave, near-infrared and visible imaging. The SDMSI requires a real-time embedded processor to fuse images and to create real-time depth maps for opportunistic uplink in sensor networks. Researchers at Embry Riddle Aeronautical University working with University of Alaska Anchorage at the Arctic Domain Awareness Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Previous work to select the most power efficient processing for the SDMSI has shown that GP-GPU co-processing is one of the most efficient approaches and the NVIDIA Corporation Tegra K1 system on chip was used for all experiments. At peak power, the system draws no more than 20 Watts for processing and for operation of all three cameras concurrently and is nominally operating at 12 Watts of power consumption during bench test measurement with a DMM for the experiments presented [1]. At this time, this is well within requirements for roof operation, but further work on power efficiency is being pursued to enable battery, alternative power source and fuel cell operation of the SDMSI for operation off-grid.…”
Section: Drone Roc For Motion Detectmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work to select the most power efficient processing for the SDMSI has shown that GP-GPU co-processing is one of the most efficient approaches and the NVIDIA Corporation Tegra K1 system on chip was used for all experiments. At peak power, the system draws no more than 20 Watts for processing and for operation of all three cameras concurrently and is nominally operating at 12 Watts of power consumption during bench test measurement with a DMM for the experiments presented [1]. At this time, this is well within requirements for roof operation, but further work on power efficiency is being pursued to enable battery, alternative power source and fuel cell operation of the SDMSI for operation off-grid.…”
Section: Drone Roc For Motion Detectmentioning
confidence: 99%
“…Image fusion requires spatial registration [3][4][5][7], matching of resolution through pyramidal up-conversion and/or down-conversion at a common aspect ratio and finally blending of pixels if a single fused image is desired rather than side-by-side comparison. Part of the challenge of performing image fusion in real-time is processing and power required, but based on previous work, we have shown this is quite possible for a system operating well below 10 to 20 Watts of total power continuously up to 30 Hz [1]. Furthermore, based on early work, we have determined that this does not require custom hardware [2].…”
Section: Image Fusion Of Multi-detector Multi-spectral Datamentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Data fusion: The sensing data acquisition from a single UAV could arguably be insufficient to meet the actual needs of coastal environmental monitoring. A possible solution approach is to combine multiple payloads, such as visible loads, infrared loads, and light detection and ranging (LiDAR), to acquire remote sensing data [139]. By fusing data from different sources with varying characteristics in the same area, the reliability of remote sensing information can be better assured.…”
Section: Marine Environmentmentioning
confidence: 99%